Mechanism and application of injectable hydrogel as carrier system in the treatment of osteoarthritis - Zhang, Bing-Gang; Liu, Qiang; Ma, Tao; Liu, Jian-Jun; Zhang, Yan; Liu, Fang; Wen, Xiao-Ming; Wang, Duo-Xian; Jiang, Wei; An, Wen-Bo (Frontiers in Bioengineering and Biotechnology, 2025)
Osteoarthritis (OA) is a disabling degenerative disease that affects synovial joints and leads to cartilage degeneration, which can cause progressive joint damage, chronic pain and functional loss. Because its specific pathogenesis is still unclear, conventional treatment methods are still difficult to achieve satisfactory therapeutic effects. Therefore, finding alternative new methods for treating OA remains a formidable challenge. Hydrogel is a kind of polymer material with good biocompatibility and biodegradability, and it is a new method for the treatment of osteoarthritis. Injectable hydrogel drug delivery platforms have shown many advantages in the treatment of OA, including improved biocompatibility, biodegradability, and low immunogenicity. Injectable hydrogels, as delivery systems, can deliver drugs to the joint cavity in a controlled manner and continuously release them, enhancing drug loading capacity and increasing sensitivity to improve therapeutic effects. This article summarizes the types of injectable hydrogels, analyzes their application as delivery systems in OA, and discusses the mechanisms of injectable hydrogels in the treatment of OA, such as anti-inflammation, anti-oxidative stress, and promotion of articular cartilage regeneration. Meanwhile, the deficiencies of injectable hydrogel drug delivery platforms in the OA field were summarized, and the future research directions in this field were discussed. Overall, injectable hydrogel drug delivery platforms show great potential in the treatment of OA. These innovative methods have brought new hope for the future treatment of OA and pointed out the direction for clinical application.